A NOTE ON ORTHOGONALITY OF THE QUASIGROUPS ARISING FROM SOME PERFECT m-CYCLE SYSTEMS - Goračinova-Ilieva, Lidija (Matematichki Bilten, 2006)
In this paper we show that the quasigroups obtained from \({k,k+1,k+2}\)-perfect \(m\)-cycle system by using the \(k\)-construction and the \((k+1)\)-construction are mutually orthogonal.